Pengaruh Kepuasan Kerja, Motivasi Kerja dan Budaya Kerja terhadap Disiplin Kerja Karyawan pada UMKM Blush Eyewear Kota Bekasi - Kharisma Cahya Dewanty; Eri Bukhari; M. Fadhli Nursal (Journal of Islamic Economics and Finance, 2024)
This study aims to measure the influence of job satisfaction, work motivation, and work culture on employee discipline at UMKM Blush Eyewear in Bekasi City. All employees of the company constitute the population of this research. The sampling method used is a saturated sample, where all members of the population are included as samples in the questionnaire distribution. A total of 40 employees participated in this study. This research employs a quantitative approach with multiple linear regression analysis, and hypothesis testing is conducted using t-tests and F-tests with a 5% significance level. The t-test results show that job satisfaction, work motivation, and work culture have a significant influence on employee discipline. The F-test results also indicate that the three variables, namely job satisfaction, work motivation, and work culture, collectively have an impact on employee discipline.